Seberapa Sulit Bagi Perusahaan di Indonesia Implementasi XBRL? (Studi Eksplorasi Perusahaan BUMN di Indonesia) - Sumiyati, Sumiyati; Ridwan, Muhammad Qomaruddin; Khairiyansyah, Khairiyansyah; Suhaidar, Suhaidar (ITB AAS INDONESIA, 2024)
This research aims to explore the factors that encourage and slow down the adoption of XBRL in Indonesia, which tends to be stagnant. The results of this research are important for understanding the factors that cause stagnation in XBRL adoption in Indonesia. The method used in this research is qualitative with semi-structured interviews with four sources consisting of companies, auditors, regulators and capital market practitioners. The results show that the use of XBRL in financial reporting should be mandatory for companies in Indonesia. Adopting XBRL in Indonesia is not difficult because the Stock Exchange has provided software that can be used directly, including the required modules. XBRL does not require special skills to run the software because it is easy and ready to use.